2010
DOI: 10.1103/physrevb.81.214203
|View full text |Cite
|
Sign up to set email alerts
|

Effective mass and tricritical point for lattice fermions localized by a random mass

Abstract: This is a numerical study of quasiparticle localization in symmetry class BD ͑realized, for example, in chiral p-wave superconductors͒, by means of a staggered-fermion lattice model for two-dimensional Dirac fermions with a random mass. For sufficiently weak disorder, the system size dependence of the average ͑thermal͒ conductivity is well described by an effective mass M eff , dependent on the first two moments of the random mass M͑r͒. The effective mass vanishes linearly when the average mass M → 0, reproduc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
44
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 37 publications
7
44
1
Order By: Relevance
“…[28], where it was found that for large N a spinless superconducting wire enters a quasi-critical region with algebraic instead of exponentially decaying transmission [29], which persists up to wire lengths L much larger than the normal-state localization length and out of range of our numerical simulations. It is also consis- tent with the approach of the two-dimensional limit, in which the one-dimensional thermal insulator transitions into a twodimensional thermal metal [30].…”
Section: Inanç Adagidelimentioning
confidence: 90%
“…[28], where it was found that for large N a spinless superconducting wire enters a quasi-critical region with algebraic instead of exponentially decaying transmission [29], which persists up to wire lengths L much larger than the normal-state localization length and out of range of our numerical simulations. It is also consis- tent with the approach of the two-dimensional limit, in which the one-dimensional thermal insulator transitions into a twodimensional thermal metal [30].…”
Section: Inanç Adagidelimentioning
confidence: 90%
“…Our findings imply that electrostatic disorder can convert the thermal insulator into a thermal metal, thereby destroying the thermal quantum Hall effect. Numerical results for this insulator-metal transition will be reported elsewhere [37].…”
Section: Prl 105 046803 (2010) P H Y S I C a L R E V I E W L E T T Ementioning
confidence: 99%
“…For strong disorder, both chiral and helical superconductors have a thermal metal-insulator transition, but the critical behavior is different: We find a localization length exponent ν ≈ 2.0, about twice as large as the known value for chiral p-wave superconductors. 13 The outline of this paper is as follows. To put our results for helical superconductors in the proper context, in the next section, we first summarize known results for chiral p-wave superconductors.…”
Section: Introductionmentioning
confidence: 99%